Fear, blame and transparency: Obstetric caregivers' rationales for high caesarean section rates in a low-resource setting. (October 2015) - Litorp, Helena; Mgaya, Andrew; Mbekenga, Columba K.; Kidanto, Hussein L.; Johnsdotter, Sara; Essén, Birgitta
Abstract: In recent decades, there has been growing attention to the overuse of caesarean section (CS) globally. In light of a high CS rate at a university hospital in Tanzania, we aimed to explore obstetric caregivers' rationales for their hospital's CS rate to identify factors that might cause CS overuse. After participant observations, we performed 22 semi-structured individual in-depth interviews and 2 focus group discussions with 5–6 caregivers in each. Respondents were consultants, specialists, residents, and midwives. The study relied on a framework of naturalistic inquiry and we analyzed data using thematic analysis. As a conceptual framework, we situated our findings in the discussion of how transparency and auditing can induce behavioral change and have unintended effects. Caregivers had divergent opinions on whether the hospital's CS rate was a problem or not, but most thought that there was an overuse of CS. All caregivers rationalized the high CS rate by referring to circumstances outside their control. In private practice, some stated they were affected by the economic compensation for CS, while others argued that unnecessary CSs were due to maternal demand. Residents often missed support from their senior colleagues when making decisions, and felt that midwives pushed them to perform CSs. Many caregivers stated that their fear of blame from colleagues and management in case of poor outcomes made them advocate for, or perform, CSs on doubtful indications. In order to lower CS rates, caregivers must acknowledge their roles as decision-makers, and strive to minimize unnecessary CSs. Although auditing and transparency are important to improve patient safety, they must be used with sensitivity regarding any unintended or counterproductive effects they might have. Highlights: Caregivers use defense strategies to avoid responsibility for high CS rates. Unnecessary CSs can be a result of dysfunctional team work. Transparency and audits may have unintended effects and lead to CS overuse. Audits need to address structural problems rather than blame individual caregivers.